L’accompagnement des enseignants à l’heure des réformes : stratégies des formateurs de terrain face à de nouvelles formes de (dé)professionnalisation - Thérèse Perez-Roux; Éric Maleyrot (Éducation et Socialisation)
In France, the "masterisation" reform of teachers training (2010) modified the place and the ground trainers’ role. The study is interested in the way some of them (PEMF) lived the implementation of this reform. It explains compromises and arrangements deployed by these teacher trainers to face these changes. The data of an investigation by questionnaire introduced this work. Research interviews were conducted with 9 PEMF. The results show a dominant deprofessionalization feeling in these trainers. They highlight at the same time a resistance movement within the group and individual strategies in continuity or in break with the previous professionalization models. Beyond these transformations, the study questions the effects of the teachers training universitarisation.